Access to Sanitation and Its Impact on Stunting in Toddlers in EastNusa Tenggara, Indonesia - Puteri, Nia Junia; Fitria, Laila (Unnes Journal of Public Health, 2025)
Background: Stunting is still one of the focuses of health problems in the world.Stunting is caused by many factors, including access to sanitation. Inadequate access to sanitation can cause infectious diseases that impair nutritional absorption intoddlers during digestion, leading to stunting. Objective: This study examines theconnection between sanitation access and stunting in East Nusa Tenggara Provincealong with its confounding variables consisting of access to drinking water, toddlerage, gender, and residence. Method: The study design was cross-sectional with asample size of 4,224 children aged 0-59 months analyzed from the 2023 Indonesian Health Survey (IHS) data. Data were analyzed using univariate, bivariate (ChiSquare test), and multivariate (multiple logistic regression analyses with a risk factormodel). Results: Studies showed households with inadequate sanitation access canincrease the risk of stunting by 1.56 compared to those with adequate sanitation access. Other factors significantly associated with stunting included toddler age, gender, and residence. The problem of access to sanitation is related to residence anddefecation behavior. Conclusion: Increasing indiscriminate defecation behavior canincrease exposure to pathogens from feces which can cause diseases such as diarrhea, resulting in malnutrition and stunted growth. To reduce stunting in East NusaTenggara Province, the government is suggested to enhance programs to expandaccess to sanitation, especially in rural areas.